Feasibility of Adopting English-Medium Instruction at Iranian Universities - Mohammad Reza Ghorbani; Sahar Zahed Alavi (Arizona State University, 2014)
This study was an attempt to explore the potential possibilities of implementing English as the medium of instruction (EMI) at Iranian universities. The sequential exploratory mixed methods design was used to collect the perspectives of both students and content-area lecturers at the state University of Bojnord through e-mail interviews and survey questionnaires developed by the researcher. The reliability of the survey questionnaire was 0.76 using Cronbach's alpha. Six undergraduate students and six lecturers were purposively selected for the interviews. As for the survey questionnaire, stratified random sampling was used to proportionately select 344 students (320 undergraduate students and 24 postgraduate students) and 36 lecturers from the accessible population. The qualitative data from the interviews were content-analyzed based on the suggestions and guidelines by Creswell (2005), Krueger (2002), and Morgan and Krueger (1998). The quantitative data from the survey questionnaires were analyzed using Statistical Package for Social Sciences (SPSS). The results revealed that most of the students and lecturers approved and supported the potential implementation of EMI at Iranian universities. The findings of this study will assist higher education authorities in policy making.